A Look at Integrated Environmental Management Plan (PIGA) in the District Department of Environment and the Comptroller of Bogotá (2015)
The issue of the environment It has been of concern worldwide, and it has generated different reactions from leaders, alarmingly leaders call the attention of countries to take measures to prevent their destruction and incidentally that of humanity. To this are held summits and conferences where nations come together to analyze the causes and consequences of environmental degradation. As expressed Germán Sánchez Pérez, Director of Department of Economics at the Autonomous University of Colombia, The main problem stems from the environmental issue It was always alien to the economic and always look separately so economists have no environmental or propose benchmarks to assess development models (2012, Page 91). The reflection on the relationship between environment and development emerges by 1972 when in Stockholm (Sweden), the interplay and conflict between environment and development was recognized and it was concluded that although certain natural resources were limited and could be exhausted, for this has not stopped the growth of the alternative would be technological, providing the solution by substitution of productive factors (2012 page 80). In subsequent meetings (Rio de Janeiro) it was recognized that the problems between environment and development exceeds the technical and environmental degradation has social, political and economic implications necessarily and in others, as in Kyoto (1997) specific agreements in which industrialized countries pledged to reduce pollution levels were signed. Colombia has not been immune to this situation and in compliance with provisions of constitutional and legal order takes steps to mitigate the damage caused to the environment as a result of activities related to the production of goods and services. This is the purpose of this investigation, which seeks to determine the importance for public entities formulating district implementation and commissioning of the Comprehensive Environmental Management Plans (CEMP) in the District Capital.